2021
DOI: 10.22452/ajba.vol14no1.3
|View full text |Cite
|
Sign up to set email alerts
|

Hype or Hope: Digital Technologies in Auditing Process

Abstract: Manuscript type: Research paper Research aims: This study aims to examine how technological,organisational and environmental (TOE) factors affect digital technologies’ utilisation and its impact on auditors’ performance. Design/Methodology/Approach: A survey was conducted on 4 large and non-large companies in Jordan, and data were retrieved from 168 external auditors. The partial least squares (PLS-3) structural equations modeling was used to analyse data and to test the proposed model. Research findings: Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Second, most of the studies on the topic were conducted in developed countries and regions, indicating the shortage of research in other contexts. This phenomenon confirms the study of Allbabidi (2021), who stated that most of the studies on adopting and using AI for auditing are undertaken in developed countries. Thus, studies must further investigate the topic in developing countries and regions (e.g.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Second, most of the studies on the topic were conducted in developed countries and regions, indicating the shortage of research in other contexts. This phenomenon confirms the study of Allbabidi (2021), who stated that most of the studies on adopting and using AI for auditing are undertaken in developed countries. Thus, studies must further investigate the topic in developing countries and regions (e.g.…”
Section: Resultssupporting
confidence: 89%
“…Considering the locations in previous publications, this review found that no study was undertaken considering two country cases (comparative analysis). Moreover, it was found that most studies undertaken on the topic are based in developed countries, confirming Allbabidi's (2021) study. In those circumstances, future researchers can contribute by undertaking comparative analysis and covering different locations, especially developing regions (like Africa) and countries.…”
Section: Resultssupporting
confidence: 79%
“…The TOE framework and Diffusion of Innovation (DOI) theory have been widely used as frameworks in studying e-commerce adoption in different countries and have found consistent empirical support (Allbabidi, 2021;Huy et al, 2012;Ilin et al, 2017;). Specifically, these theories have been used in prior empirical research due to their popularity in literature and they have been found to provide a broad understanding of the adoption of new technology such as e-commerce (Qashou & Saleh, 2018;Khoo et al, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…As auditors, they should be capable of carrying out a number of tasks competently, as well as the fundamental skills and knowledge required to complete each task (Komneni c, 2009). In the context of technology, highly competent persons tend to be more confident in the use of technology tools; they enjoy using them and appreciate their usefulness (Allbabidi, 2021;Al-Hattami, 2023). IT audit competency plays a crucial role in ensuring the effectiveness and efficiency of IT systems within organizations.…”
Section: It Audit Competencymentioning
confidence: 99%